The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1038/bjc.1998.446
|View full text |Cite
|
Sign up to set email alerts
|

Effects of retinoic acid and fenretinide on the c-erbB-2 expression, growth and cisplatin sensitivity of breast cancer cells

Abstract: Summary We investigated the effects of all-trans retinoic acid (ATRA) and fenretinide (4-HPR) on c-erbB-2 expression in SK-BR-3, and MCF-7 breast cancer cells and on the growth, differentiation, apoptosis and cisplatin (CDDP) sensitivity of SK-BR-3 cells. It has been reported that oestrogen inhibits c-erbB-2 in oestrogen receptor-positive breast cancer cells. Using ELISA, Westem and Northem analysis we have demonstrated that ATRA and 4-HPR exert similar effects down-regulating c-erbB-2 protein and mRNA in c-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…Interestingly, all-trans retinoic acid (ATRA) and fenretinide (4-HPR) have been shown to downregulate ErbB2 protein and mRNA in ErbB2-overexpressing SKBR3 and BT474 breast cancer cells as well as in MCF-7 cells that express lower levels of ErbB2. Moreover, 4-HPR plus cisplatin has been shown to be more e ective in inhibiting the growth of ErbB2-overexpressing cells than either agent alone (Grunt et al, 1998). Recently, retinoic analogues were also shown to delay mammary tumor development in cneu transgenic mice (Rao et al, 1999).…”
Section: Downregulation Of Erbb2 By Retinoic Acidmentioning
confidence: 99%
“…Interestingly, all-trans retinoic acid (ATRA) and fenretinide (4-HPR) have been shown to downregulate ErbB2 protein and mRNA in ErbB2-overexpressing SKBR3 and BT474 breast cancer cells as well as in MCF-7 cells that express lower levels of ErbB2. Moreover, 4-HPR plus cisplatin has been shown to be more e ective in inhibiting the growth of ErbB2-overexpressing cells than either agent alone (Grunt et al, 1998). Recently, retinoic analogues were also shown to delay mammary tumor development in cneu transgenic mice (Rao et al, 1999).…”
Section: Downregulation Of Erbb2 By Retinoic Acidmentioning
confidence: 99%
“…However, few previous studies reported such effects of retinoic acid on other cytotoxic drugs, including cisplatin, etoposide, paclitaxel, and gemcitabine (Formelli and Cleris, 1993;Shalinsky et al, 1996;Grunt et al, 1998;Kalemkerian and Ou, 1999;Pettersson et al, 2001). The basis for those studies was the known antitumor effects of retinoic acids.…”
mentioning
confidence: 99%
“…Laboratory results demonstrated that 4HPR increases the sensitivity of breast cancer cells to tamoxifen, interferon-ß and cisplatinum [14,15,18]. Here, we demonstrate that 4HPR, at a pharmacologically achievable dose, which is approximately 1 ÌM [21], can effectively sensitize HER2/neu-overexpressing breast cancer cells to ATRA.…”
Section: Discussionmentioning
confidence: 72%
“…4HPR has been shown to repress HER2/neu expression [16,17]. By suppressing the expression of HER2/neu, 4HPR increased the sensitivity of HER2/neu-overexpressing breast cancer cells to cisplatinum [18]. Here we determine whether 4HPR, by suppressing HER2/neu expression, could sensitize breast cancer cells to ATRA.…”
Section: Introductionmentioning
confidence: 98%